Interleukin-6 and indoleamine-2,3-dioxygenase as potential adjuvant targets for Papillomavirus-related tumors immunotherapy - Pagni, Roberta Liberato; Souza, Patrícia da Cruz; Pegoraro, Rafael; Porchia, Bruna Felício Milazzotto Maldonado; da Silva, Jamile Ramos; Aps, Luana Raposo de Melo Moraes; Silva, Mariângela de Oliveira; Rodrigues, Karine Bitencourt; Sales, Natiely Silva; Ferreira, Luís Carlos de Souza; Moreno, Ana Carolina Ramos (Frontiers in Immunology, 2022)
High-risk Human papillomavirus (HPV) infections represent an important public health issue. Nearly all cervical malignancies are associated with HPV, and a range of other female and male cancers, such as anogenital and oropharyngeal. Aiming to treat HPV-related tumors, our group developed vaccines based on the genetic fusion of the HSV-1 glycoprotein D (gD) with the HPV-16 E7 oncoprotein (gDE7 vaccines). Despite the promising antitumor results reached by gDE7 vaccines in mice, combined therapies may increase the therapeutic effects by improving antitumor responses and halting immune suppressive mechanisms elicited by tumor cells. Considering cancer immunosuppressive mechanisms, indoleamine-2,3-dioxygenase (IDO) enzyme and interleukin-6 (IL-6) stand out in HPV-related tumors. Since IL-6 sustained the constitutive IDO expression, here we evaluated the therapeutic outcomes achieved by the combination of active immunotherapy based on a gDE7 protein-based vaccine with adjuvant treatments involving blocking IDO, either by use of IDO inhibitors or IL-6 knockout mice. C57BL/6 wild-type (WT) and transgenic IL-6-/- mice were engrafted with HPV16-E6/E7-expressing TC-1 cells and treated with 1-methyl-tryptophan isoforms (D-1MT and DL-1MT), capable to inhibit IDO. In vitro, the 1MT isoforms reduced IL-6 gene expression and IL-6 secretion in TC-1 cells. In vivo, the multi-targeted treatment improved the antitumor efficacy of the gDE7-based protein vaccine. Although the gDE7 immunization achieves partial tumor mass control in combination with D-1MT or DL-1MT in WT mice or when administered in IL-6-/- mice, the combination of gDE7 and 1MT in IL-6-/- mice further enhanced the antitumor effects, reaching total tumor rejection. The outcome of the combined therapy was associated with an increased frequency of activated dendritic cells and decreased frequencies of intratumoral polymorphonuclear myeloid-derived suppressor cells and T regulatory cells. In conclusion, the present study demonstrated that IL-6 and IDO negatively contribute to the activation of immune cells, particularly dendritic cells, reducing gDE7 vaccine-induced protective immune responses and, therefore, opening perspectives for the use of combined strategies based on inhibition of IL-6 and IDO as immunometabolic adjuvants for immunotherapies against HPV-related tumors.